2020
DOI: 10.1108/cg-03-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

When do women on board of directors reduce bank risk?

Abstract: Purpose This study aims to examine the relationship between female directors and bank risk. In particular, whether such a relationship varies across sound or unsound banks and with or without a critical mass of female directors is tested. Design/methodology/approach Using a sample of 215 listed banks from 40 countries over the period 2008–2016, this study carries out panel data analyses and tests all the model specifications on four different measures of risk (common equity ratio, leverage, NPLs ratio and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 83 publications
2
39
0
Order By: Relevance
“…Hence, the presence of female directors is related to more prudent CAR for the same level of risk, which shows greater bank stability. These findings are consistent with recent studies by Birindelli et al (2020), Owen and Temesvary (2018) and Farag and Mallin (2017), who demonstrated that a critical mass of female directors reduces bank risk when banks are sound. In line with these studies, we implicitly prove that the relationship between female directors and bank risk-taking depends on bank soundness.…”
Section: Findings and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, the presence of female directors is related to more prudent CAR for the same level of risk, which shows greater bank stability. These findings are consistent with recent studies by Birindelli et al (2020), Owen and Temesvary (2018) and Farag and Mallin (2017), who demonstrated that a critical mass of female directors reduces bank risk when banks are sound. In line with these studies, we implicitly prove that the relationship between female directors and bank risk-taking depends on bank soundness.…”
Section: Findings and Discussionsupporting
confidence: 93%
“…The results of their investigation indicate that a higher percentage of women on bank boards is related to lower risk-taking. Using a sample of 215 listed banks from 40 countries from 2008 to 2016, Birindelli et al (2020) showed that female directors have a significant and positive role in reducing risk when banks are sound. This finding supports the view of a negative relationship between the presence of females on the bank's board and its risk-taking behavior.…”
Section: Percentage Of Females On Boards Of Directors and Bank Risk-t...mentioning
confidence: 99%
“…We use other dependent variables ( CAMEL ) than the Z-score to check the robustness of our findings. Natural logarithmic transformations of the three non-index variables (bank age, bank size and GDP ) are used to better estimate a normal distribution (Birindelli et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to studies focused on corporate governance and firm performance, the existing literature on the association between corporate governance and the level of risk faced by firms is relatively small (Alam and Shah, 2013; Chang et al , 2015; Alfiero and Venuti, 2016). Studies on the topic mainly investigate the influence exerted by the board of directors and by the ownership structure on corporate risk-taking, showing mixed results (Morck et al , 1999; Nguyen, 2011; Mathew et al , 2016; Birindelli et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%